Integrating palliative care and hospice services in long term care: an eightfold path health policy analysis - Amil Kusain Tan (International Journal of Public Health Science (IJPHS), 2019)
It is evident in the literature that as near end of life approaches, health expenditure increases. The rehospitalization and underutilization of palliative and hospice services add to the burgeoning health cost. There is a lack of support for patients with advanced illness in long-term care facilities. This paper aims to provide a comprehensive review of the problem and assess alternatives to reduce readmission among patients with advanced disease and those who are at the end of life.  This paper adapted Bardach’s Eightfold Path analysis as a guide to analyzing the problem using a case study approach. The article discussed the issues, reviewed the literature for evidence, provided the alternatives, identified criteria, evaluated projected outcomes, discussed the trade-offs of adopting the policy, and provided a recommendation. In conclusion, integration of palliative and hospice care services across the continuum of long-term care is a viable alternative policy to address the problem.